2016
DOI: 10.3765/plsa.v1i0.3725
|View full text |Cite
|
Sign up to set email alerts
|

Abstraction of phonological representations in adult nonnative speakers

Abstract: Abstract. Perception of nonnative contrasts by adult second language (L2) learners is affected by native language phonology. The current study contrasted predictions from two models of L2 phonological acquisition that focus on different representational levels as the origin of native language transfer: the abstract categorization level from the Perceptual Assimilation Model for L2 learners (PAM-L2; Best & Tyler, 2007) and the phonetic level from the Automatic Selective Perception model (ASP; Strange, 2011). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Our starting point is the fuzzy lexicon hypothesis , according to which the phonolexical and/or phonological representations of newly learned L2 words are initially underspecified, or fuzzy (Cook, 2012 ; Cook and Gor, 2015 ; Cook et al, 2016 ; Lancaster and Gor, 2016 ). This fuzziness leads to inaccuracies in auditory speech perception.…”
Section: Introductionmentioning
confidence: 99%
“…Our starting point is the fuzzy lexicon hypothesis , according to which the phonolexical and/or phonological representations of newly learned L2 words are initially underspecified, or fuzzy (Cook, 2012 ; Cook and Gor, 2015 ; Cook et al, 2016 ; Lancaster and Gor, 2016 ). This fuzziness leads to inaccuracies in auditory speech perception.…”
Section: Introductionmentioning
confidence: 99%
“…L2 phonolexical representations have repeatedly been found to lack relevant phonetic detail: that is, phonetic categories are ‘fuzzily’ or ‘weakly’ encoded into these representations. This is generally reflected in slower and more error-prone word recognition in the L2 compared to the L1 (Cook, 2012; Cook & Gor, 2015; Cook, Pandzda, Lancaster & Gor, 2016; Lancaster & Gor, 2016).…”
mentioning
confidence: 99%
“…All in all, the present study provides a first approximation to the issue of how the lexicon and speech perception intertwine in the phonolexical encoding of difficult L2 contrasts from an item-centered perspective. Challenging L2 phonological contrasts introduce an additional level of "fuzziness" to L2 lexical representations, which are known to already be fuzzy because of the inherent characteristics of L2 learning itself (Cook and Gor, 2015;Cook et al, 2016;Lancaster and Gor, 2016). Previous studies have shown that, for non-native phonological contrasts in which the two L2 phones differ in how well they match L1 categories, the difficulties brought about by such phones are not symmetric (Weber and Cutler, 2004;Cutler et al, 2006;Darcy et al, 2013;Darcy, 2017, 2018;Peperkamp, 2019, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…First, the relatively impoverished input translates into reduced exposure to individual L2 words, which often prevents their robust integration into long-term memory (Gollan et al, 2008) and almost invariably results in smaller vocabulary sizes in the L2 when compared with the native language (L1; Nation, 2006). Secondly, for words that become part of the L2 lexicon, the scarcity of L2 input results in the newly established lexical representations being phonologically vague or "fuzzy" (Cook and Gor, 2015;Cook et al, 2016;Lancaster and Gor, 2016). This means that the encoding of phonetic categories into lexical representations (i.e., phonolexical encoding) is not as robust as that of native lexical items, which greatly contributes to L2 spoken word recognition being rather error-prone and characterized by spurious lexical competition (e.g., Weber and Cutler, 2004;Cook et al, 2016).…”
Section: Introductionmentioning
confidence: 99%